Melacak Akar Geneologi Kritik Hadis: Studi atas Aplikasi Kritik Sanad dan Matan Masa Rasul serta Sahabat - Arfian, Arfian (DIRAYAH : Jurnal Ilmu Hadis, 2020)
This research discusses the study of criticism of hadith (naqd al-hadîts) both sanad and matan. The discussion includes the methodology and application of the criticism of sanad and matan seen in the period of the Prophet and his companions. In this study the writer used a historical approach, and in analyzing the data the writer used the descriptive-analysis method. Regarding the study of hadith criticism, it has actually been carried out since the time of the Prophet and his companions. However, the sanad and matan criticisms in the initial phase have not been formulated systematically and methodologically as in the final phase (al-Muta`akhirîn). This is because there is still a prophet figure as an authoritative source to ask (clarify) what news a friend has heard. After the death of the Prophet Muhammad, problems in the hadith have not yet emerged, besides that there are still friends who always maintain their honesty and do not want to lie on behalf of the Prophet Muhammad. Criticism of the hadith at the time of the companions focused on testing the truth of whether the Prophet actually conveyed the hadith or not. Penelitian ini membahas tentang studi kritik hadis (naqd al-hadîts) baik sanad maupun matan. Pembahasan yang ada di dalamnya meliputi metodologi dan aplikasi kritik sanad dan matan yang dilihat pada periode Nabi dan sahabat. Dalam kajian ini penulis menggunakan pendekatan historis, dan dalam melakukan analisis data penulis menggunakan metode deskriptif-analisis. Berkaitan kajian kritik hadis sebenarnya telah dilakukan sejak masa Nabi dan sahabat. Akan tetapi kritik sanad dan matan pada fase awal belum diformulasikan secara sistematis dan metodologis sebagaimana fase akhir (al-Muta`akhirîn). Hal ini karena masih ada sosok nabi sebagai sumber otoritatif untuk bertanya (mengklarifikasi) kabar yang didengar sahabat. Pasca wafat Nabi Muhammad SAW, problematika dalam hadis juga belum banyak bermunculan, selain itu masih terdapat sahabat yang senantiasa menjaga kejujurannya dan tidak mau berbohong atas nama Rasulullah SAW. Kritik hadis pada masa sahabat tertuju pada uji kebenaran apakah Rasulullah benar-benar menyampaikan hadis tersebut atau tidak.